THEMATIC ELECTRONIC MAPS FOR INTELLIGENT TRANSPORTATION SYSTEMS IN CITIES - Kuljonov Farkhod Berdiyorovich; Urokov Asliddin Hushvaqtovich (European Science Publishing, 2025)
This article highlights the role and importance of thematic electronic maps in the effective management of intelligent transportation systems in cities. It analyzes the possibilities of monitoring, managing, and modeling traffic flows through electronic maps created based on modern GIS (Geographic Information System) technologies. The paper also examines issues related to optimizing urban infrastructure, improving road traffic safety, and reducing environmental impacts with the help of electronic maps. In addition, the crucial role of information and communication technologies in the development of intelligent transportation systems is emphasized. The research results serve as a basis for developing recommendations aimed at modernizing urban transportation systems.
Keywords: Intelligent transportation systems, thematic electronic maps, urban infrastructure, transport logistics, digital mapping, traffic management, GIS technologies, urban planning, transport flow modeling.